El software Crocodile y su relación en el aprendizaje de la física en el bloque curricular electricidad y magnetismo, aplicado a los estudiantes de bachillerato general unificado de la unidad educativa Tuntatacto, año lectivo 2015 - 2016. - Padilla Muñoz, Monserrath Amparo (2017)
The present work research is about of Crocodile software method and the relation with the learning of the physic in the curricular block of electricity and Magnetism aplied to the students of Bachillerato General Unificado Unidad Educatica “Tuntatacto” in the academic period 2015 – 2016, considered as a problem the low academic performance and lack of interest of the students, as well as the little importance given by teachers to the use of Tics as a didactic resource in teaching, The educational software Crocodile is a resource that achieve better the attention and concentration of the students, hence the importance of using it in the contents of the current curricular block in the subject of Physic – Chemistry. The methodology was used on a pre-experimental design it was verified with the T for relater samples statistic where a P_value = 0.000000062 < alpha = 0.05, whereby the null hypothesis (H0) was rejected, arriving at the conclusion that the use of TICS as a didactic resource related, arriving at the conclusion that the use of ICT as a didactic resource improved the academic performance obtained in the first partial after the application of the software so that it can be determine the strengthening of theoretical knowledge with virtual practice. So it is recommended the use of tics and didactic guide at the time of imparting knowledge.